Empowering Women Producers through Value Chain Development in Commercial Vegetable Farming for Improved Livelihood and Food Security - Ghimire, Dhruba Raj (Journal of Forest and Livelihood, 2020)
Although agriculture and forestry sector provides employment to almost two thirds of households, the commercialisation of farming is in its rudimentary stage in Nepal. On the other hand, 28.6 percent of Nepal’s population is multi-dimensionally poor and 48 per cent households are food insecure. Given that women’s workload and responsibility in the household is significant, promoting economic opportunities for them can make a big difference in the household livelihood and food security. This research investigated the effectiveness of local value chain process in commercialisation of vegetables among targeted women producers in Kailali district of Nepal, towards improved livelihoods and food security. With post-positivism paradigm, this research capitalised QUAN-qual methodology. Based on comparative performance data of 1,469 women producers engaged in vegetable farming, there has been almost three times increase in production of commodity and 78 per cent increase in average revenue of the producers within a short span of time, which is encouraging.